Empirically derived models of strategic decision‐making processes - Shrivastava, Paul; Grant, John H. (Strategic Management Journal, 1985)
Abstract This paper reports on an empirical study of strategic decision‐making processes and organizational learning in 32 business organizations facing complex environments. The decision processes were found to vary in four prototypical patterns described here as the strategic decision‐making models. These models are proposed as an initial step towards the development of a taxonomy of strategic decision processes. The relationships between strategic decision‐making models and organizational learning systems that support them are explored. These models may help researchers to conceptualize and practitioners to manage strategy formulation processes in organizations.